Design, detail analysis and performance testing of uav propulsion system - Che Muhammad Ridhwan, Che Hashim (2012)
This project report is being conduct because the use of an Unmanned Aerial Vehicle (UAV) is getting popular among people either to have fun or study but the choices of powerplant are not fully deployed (in term of operational and performance sizing) and thus limiting the selection. The objective of this project is to propose a design, detail analysis and performance testing of an Unmanned Aerial Vehicle (UAV) propulsion system. In this study, the test bed model was designed to test the nitro engine Radio Control (RC) which is model of 46-LA OS Engine Series of aircraft performance which are four performance parameters that was studied such as thrust, available power and shaft brake power, propulsive efficiency and brake specific fuel consumption thus the performance parameters value can be calculated by measure the unknown value of parameters regarding to the equation involves within the range 2000 to 16000 RPM of engine speed by setting the test bed design with suitable apparatus. From this experiment, the result shows that the fabricated test bed can be use to study the engine performance and performance parameters are directly proportional to the engine speed which is mean the faster the speed of engine effected the increasing of performance parameters. As a conclusion, even without testing the engine to the real body of aircraft, all the engine performance parameter can be calculated from this experiment, and it will reduce the time and cost.